Soil hydraulic properties and field-scale hydrology as affected by land-management options - Rahman, Atiqur; Amin, M. G. Mostofa (Universitas Sebelas Maret, 2023)
Recurring puddling for long-term rice cultivation forms a plow pan at a particular soil depth, which alters soil hydraulic properties, field-scale hydrology, and nutrient persistence in the soil. This experiment aimed to assess the impact of long-term rice cultivation on root-zone soil hydraulic properties and field-scale hydrology. Soil core samples were collected from four land management options namely, rice‒rice, non-rice, rice and non-rice, and field ridge, at two sites, one with loam and another with silt-loam soil. The soil cores were sampled for each 10 cm layer up to 100 cm depth from three locations of each rotation at both sites. Soil hydraulic parameters were estimated using a pedotransfer function based on the measured bulk density and soil texture. A mathematical model named HYDRUS-1D predicted infiltration, percolation, and surface runoff with the estimated hydraulic properties for three extreme rainfall events, i.e., 3.33, 5, and 6.66 cm hr-1, during a 3-hour period. A plow pan was found at 20–30 cm soil depth for all the land management options but not for the field ridge. The plow pan of the rice‒rice rotation had the highest bulk density (1.53 g cm-3) and the lowest hydraulic conductivity (17.56 cm day-1). However, the top 10 cm soil layer in the rice–rice field had the lowest bulk density (0.93 g cm-3). At both sites, the field ridge had higher infiltration and percolation and lower runoff than other rotations. The study reveals that the field-ridge area of a rice field can be the main water loss pathway. Phosphorus concentration in the rice-rice rotation decreased from 7.7 mg kg-1 in the 10-cm soil layer to 2.49 mg kg-1 in the 100-cm layer. These findings will facilitate making better water management decisions.